Crime dye guns : lasers - Hobel-Leiterman Productions ([New York] : Hobel Leiterman Productions, 1976)
The police officer is presented as a human being, with all the flaws and imperfections of the ordinary citizen. Thus, we see the officer as someone who needs understanding and support to help him do his job more effectively.
Converted into VHS 1/2 in. and DVD.
Keywords: Crime prevention; Law enforcement